2022
DOI: 10.3390/antiox11112169
|View full text |Cite
|
Sign up to set email alerts
|

The Greening of Anthocyanins: Eco-Friendly Techniques for Their Recovery from Agri-Food By-Products

Abstract: In recent years, several steps forward have been made toward a more sustainable approach for the extraction of bioactive compounds from plant materials based on the application of green extraction principles. It is currently recognized that waste and by-products deriving from agriculture and food industries still contain a wide array of high value-added substances, which can be re-used to obtain new products with various applications in the food, supplement, pharmaceutical, and cosmetic industries. Anthocyanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 100 publications
1
9
0
Order By: Relevance
“…The standard peaks of Del-delphinidin-3-mono glucoside (D3G) and Petunidin-3-mono glucoside (P3G) were observed at 3.1 and 5.1 min, respectively (S1 and S2). This phenomenon has been documented previously that characterized anthocyanin profiles of red table grape cultivars [ 48 ].…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The standard peaks of Del-delphinidin-3-mono glucoside (D3G) and Petunidin-3-mono glucoside (P3G) were observed at 3.1 and 5.1 min, respectively (S1 and S2). This phenomenon has been documented previously that characterized anthocyanin profiles of red table grape cultivars [ 48 ].…”
Section: Resultssupporting
confidence: 66%
“…This study further indicated that Delphinidin-3-glucoside was the primary anthocyanin that has been linked to numerous health benefits, such as antidiabetic and antiradical activities. Furthermore, Pomar, Novo and Masa [ 48 ] estimated a typical HPLC chromatogram of anthocyanin at 546 nm. The authors calculated the chemical structure of anthocyanins by hydrolysis and chromatographic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The extraction of specialized metabolites from plant material is influenced by several factors, such as the solvent type, the pH, the chemical stability of the target molecules, and specific operative parameters of the instrumentation. Temperature, time, and the solid-to-liquid ratio are among the most impacting parameters on polyphenol extraction [ 37 , 38 , 39 ]; hence, they were chosen as quantitative factors for the optimization of anthocyanin recovery from grape pomace through the DoE.…”
Section: Resultsmentioning
confidence: 99%
“…scCO 2 is a commonly used extractant in the pharmaceutical and natural products industries [69][70][71][72][73]. It is a non-toxic, non-flammable, and environmentally friendly solvent [74,75], and it can be easily removed by depressurization and evaporation [76][77][78]. The extracts were obtained with scCO 2 at 50 • C under 2000 (a) and 6000 PSI (b) (Table 3).…”
Section: Extractionmentioning
confidence: 99%